2017
DOI: 10.1159/000485136
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy among Systemic Lupus Erythematosus Patients: Insights from a Large Database Analysis

Abstract: Objective: Epilepsy is characterized by a relevant epidemiological and clinical burden. In the extant literature, an increased risk of seizures has been described in several inflammatory/autoimmune disorders, including systemic lupus erythematosus (SLE). However, so far, relatively few and small size-based studies have been conducted. We aimed to investigate the link between seizure and SLE utilizing a large sample of subjects and extensive data analysis. Methods: Patients with SLE were compared with age- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 33 publications
(33 reference statements)
0
11
0
3
Order By: Relevance
“…Various reports indicated a high prevalence of seizures among people with SLE (prevalence:1.6%-16%) [3,8,[36][37][38][39][40][41]; and from studies including controls they seem higher than in the general population [8,[38][39][40][41]. A recent cross sectional study with over 5000 people with SLE and over 25,000 controls found epilepsy 4.7 times more likely in the SLE cohort (95% CI: 3.9-5.8%) [39]. One retrospective cohort study also reported that SLE was associated with 5.6-fold increased risk of epilepsy [41].…”
Section: Systemic Lupus Erythematosus (Sle)mentioning
confidence: 99%
“…Various reports indicated a high prevalence of seizures among people with SLE (prevalence:1.6%-16%) [3,8,[36][37][38][39][40][41]; and from studies including controls they seem higher than in the general population [8,[38][39][40][41]. A recent cross sectional study with over 5000 people with SLE and over 25,000 controls found epilepsy 4.7 times more likely in the SLE cohort (95% CI: 3.9-5.8%) [39]. One retrospective cohort study also reported that SLE was associated with 5.6-fold increased risk of epilepsy [41].…”
Section: Systemic Lupus Erythematosus (Sle)mentioning
confidence: 99%
“…Data available from CHS database included age, sex, smoking status, SES (based on the subject's residence area poverty index, divided into 3 categories – low, medium and high) and diagnosis of chronic diseases, including input date into CHS database. The validity of the diagnosis in the registry was found to be high in previous studies . A control patient matched by age and sex was randomly selected for each FMF case.…”
Section: Methodsmentioning
confidence: 99%
“…The validity of the diagnosis in the registry was found to be high in previous studies. 19,20 A control patient matched by age and sex was randomly selected for each FMF case. The control group was selected from the list of CHS members, excluding patients with FMF.…”
Section: Me Thodsmentioning
confidence: 99%
“…Волчаночный нефрит представляет собой одно из самых серьезных осложнений СКВ с учетом повышенной заболеваемости, развития терминальной почечной недостаточности и высокого уровня смертности [2], поэтому раннее подозрение и выявление заболевания на уровне первичной медицинской помощи имеет первостепенное значение. Нейропсихиатрическая волчанка также является тяжелым и жизнеугрожающим фенотипом СКВ [21] и охватывает широкий спектр неврологических и психиатрических проявления различной степени тяжести, такие, как судороги, когнитивная дисфункция, психоз и депрессия [69]. Таким образом, семейные врачи должны вовремя оценить такие случаи и заподозрить СКВ для раннего назначения специфического лечения [69].…”
Section: какие наиболее тяжелые формы скв?unclassified
“…Нейропсихиатрическая волчанка также является тяжелым и жизнеугрожающим фенотипом СКВ [21] и охватывает широкий спектр неврологических и психиатрических проявления различной степени тяжести, такие, как судороги, когнитивная дисфункция, психоз и депрессия [69]. Таким образом, семейные врачи должны вовремя оценить такие случаи и заподозрить СКВ для раннего назначения специфического лечения [69].…”
Section: какие наиболее тяжелые формы скв?unclassified